KABA LAMAMANG TANJUNG AMPALU: SEBUAH PENELUSURAN KEARIFAN LOKAL - Irwanto, Irwanto (Diksi, 2020)
(Title: Kaba Lamamang Tanjung Ampalu: a Search for Local Wisdom). Kaba is a type of oral literature typical of the West Sumatra region, ethnic Minangkabau. Kaba is a story told by a Kabaist with accompaniment of fiddle music. Kaba's literary strength is largely determined by the ability of the Kabaist. Kaba Lamang Tanjung Ampalu is played by Hasan Basril, one of the interesting research subjects to study. Issues of value or local wisdom in Kaba Lamang Tanjung Ampalu are considered interesting and need to be raised. The reason, Kaba as oral literature and values of life as a social phenomenon become an interrelated element. As a human's creation, Kaba will convey the values contained to the audience, so that Kaba can influence the listener's mindset. This reasoning is in accordance with the opinion of Wallek and Warren (1989) that in literature (Kaba) there is a value of life. The descriptive analytical research method explains the meaning of the contents of symbolic interactions that occur in communication events so that the contents of Kaba can be understood appropriately. As a result, this study shows that there are 7 local wisdoms in Kaba Lamang Tanjung Ampalu; the value of local wisdom relates to livelihoods, equipment, values of knowledge, religious systems, arts, social systems, and language and literature.Keywords: kaba, local wisdom, Minangkabau ethnicity